Role of Programmed Ventricular Extrastimulation in Differentiating Atrioventricular Nodal Re-entrant and Atrioventricular Re-entrant Tachycardias in Supraventricular Tachycardias - Najam, Momina; Shabbir, Muhammad; Khan, Qurban Hussain; Rauf, Atif; Ur Rehman, Waheed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the diagnostic effectiveness of Programmed Ventricular Extrastimulus (PVE) during supraventricular tachycardia (SVT) in differentiating atrioventricular nodal re-entrant tachycardia (AVNRT) from atrioventricular re-entrant tachycardia (AVRT).Study Design: Analytical Cross-Sectional StudyPlace and Duration of Study: Electrophysiology Department, Armed Institute of Cardiology/National Institute of Heart Disease, Rawalpindi, Pakistan, from Mar to Aug 2025Methodology: A total of 180 adult patients (aged ≥18 years) of either gender with suspected or documented supraventricular tachycardia (SVT) or inducible tachycardia during an electrophysiology (EPS) study were enrolled. Both ventricular entrainment and PVE (V2) pacing techniques were applied to record electrophysiological parameters, including stimulus-to-atrial minus ventriculoatrial (SA-VA) time and post-pacing interval minus tachycardia cycle length (PPI–TCL). Based on EPS findings, patients were classified into two groups: AVNRT (n=90) and AVRT (n=90).Results: Among 180 patients, the AVNRT group included 53 males (58.9%), and the AVRT group had 64 males (71.1%). The mean age was 45.50 ± 15.31 years in the AVNRT group and 34.29 ± 11.78 years in the AVRT group (p